The PHARMACOGNOSTICAL, PHYSICOCHEMICAL AND HIGH-PERFORMANCE THIN LAYER CHROMATOGRAHY (HPTLC) EVALUATION OF ERANDAMULADI KALKA CHOORNA - Swathi N.; Anup B. Thakar; Harisha C.R.; V.J. Shukla (Journal of Biomedical and Pharmaceutical Research, 2020)
Introduction: Erandamuladi Niruha Basti is mentioned in Charaka Samhita which is indicated in Trika, Prishta Shoola (low back ache) and acts as Maruta Nigraha. Low backache is the most common ailment in today’s busy life. Erandamuladi Kalka used in Basti contains 9 drugs in which most of the drugs are having Ushna Veerya and are Shoolahara in nature. Method: Sookshma Choorna of Erandamuladi Kalka was evaluated for their pharmacognostic and pharmaceutical analysis. Results: Pharmacognostic study showed the presence of contents such as cluster crystal of Hapusha, starch grains of Musta, spiral vessels of Bala etc. Physico-chemical analysis showed that the loss on drying 6.28%, Ash value 13.26%, Water soluble extract 19.34%, Alcohol soluble extract 4.24%, pH 7.0 Discussion and Conclusion: The pharmacognostical and phytochemical analysis of Erandamuladi Kalka Choorna confirmed the purity and genuinity of drug, which can be espoused for laying down the standards of it. Keywords: Erandamuladi Kalka Choorna, Pharmacognostic, Phytochemical analysis, HPTLC